Narrow long Josephson junctions - Koval, Yury; Wallraff, Andreas; Fistul, Mikhail; Thyssen, N.; Kohlstedt, H.; Ustinov, Alexey (IEEE Transactions on Applied Superconductivity, 1999)
Long Josephson junctions of width down to less than 0.3 pm are fabricated using electron beam lithography. The junctions are made in niobiumaluminum-oxide trilayer technology using cross-linked PMMA for insulation. We measured the fluxon penetration field, the magnetic field period of the critical current modulation, and the Fiske step voltages of the junctions. A strong dependence of these quantities on the junction width is observed. Assuming a general-type relation between the spatial derivative of the phase and the spatial variation of the magnetic field along the plane of the junction, we derive a scaling relation between the measured quantities depending on the junction width. The derived relation is consistent with the experimental data. © 1999 IEEE.
UnivIS-Import:2015-03-05:Pub.1999.nat.dphy.IAP.pephys.narrow